(untitled) (The Review of Diabetic Studies, 2025)
Background: Saudi Arabia’s Vision 2030 emphasizes preventive care and the effective management of chronic diseases, necessitating evidence-based strategies to enhance healthcare delivery. Community Health Needs Assessments (CHNAs) are crucial in identifying population-specific health priorities, service gaps, and areas for policy and system improvement. Objective: This study aimed to assess the health needs of Makkah residents through a community-based approach, identifying prevalent health conditions, service delivery gaps, and community concerns to inform targeted health interventions.Methods: A cross-sectional study was conducted from January to March 2025 across ten hospitals within the Makkah healthcare cluster. Using a convenience sampling method, 2,479 residents aged 18 and above participated by completing a digital questionnaire covering socio demographics, community health assets, health concerns, and healthcare service perceptions. Data were analyzed using descriptive statistics. Results: Among participants, 63% were male and 94.5% were Arab, with most aged between 35 and 64. Chronic disease prevalence was highest in the Al-Shara`e sector (43.5%). Diabetes mellitus was most prevalent in the Khoules sector (28.8%), and hypertension was common in Al-Jamum (25.8%). The community expressed major concerns about healthcare provider availability (48.6%) and specialist access (39.8%). Youth prioritized obesity (43.9%) and smoking, while the elderly cited access to home health services and the ability to meet daily needs as top concerns. Key service gaps included specialist clinics, timely appointment availability, and mental health services. Conclusion: The CHNA highlights significant disparities in chronic disease burden and healthcare accessibility across Makkah’s regions. Findings underscore the need for tailored, community-driven health initiatives focused on chronic disease prevention, provider availability, and improved service delivery. These results provide a foundation for future health planning and policy efforts aligned with national health goals.